Edge plasma study using a fast visible light camera in the COMPASS tokamak. (September 2017) - Jirman, Tomáš; Peterka, Matěj; Seidl, Jakub; Cavalier, Jordan; Weinzettl, Vladimír; Brochard, Frédéric; Cahyna, Pavel; Harrison, James; Imrisek, Martin; Kirk, Andrew; Panek, Radomír
Abstract: Fast SA5 camera operating in the visible range has been installed on the COMPASS tokamak and used to study oscillations of visible light emission at plasma periphery. The work proved capability of the camera to detect several types of oscillatory modes in the COMPASS plasma in the frequency range 500 Hz – 50 kHz, such as sawteeth ( 400 Hz), tearing mode ( 10 kHz) or geodesic acoustic mode ( 30 kHz). Moreover, method for visualising their spatial structure has been proposed and tested on the case of a rotating 10 kHz tearing mode. In addition, the camera has been used as a tool to study time evolution of divertor strike point splitting induced by resonant magnetic perturbations.